Expressing a Short Tandem Target Mimic (STTM) of miR164b/e-3p enhances poplar leaf serration by co-regulating the miR164-NAC module - Wang, Jieyu (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.